A Study on the Sufficient Conditional and the Necessary Conditional With Chinese and French Participants - Shao, Jing; Tikiri Banda, Dilane; Baratgin, Jean (Frontiers in Psychology, 2022)
According to the weak version of linguistic relativity, also called Sapir-Whorf hypothesis, the characteristics of one’s native language influence one’s world view and perception. We decided to test this hypothesis on the sufficient conditional and the necessary conditional which are expressed differently in Chinese and French. In Chinese, connectors for both sufficient and necessary conditionals exist and are used in everyday life, while in French, there is only a connector for the sufficient conditional. Conforming to linguistic relativity, better logic performance on the necessary conditional was expected with Chinese participants than with French participants. Our second hypothesis is that there should be a better performance on the sufficient conditional than on the necessary conditional with Chinese and French participants. Indeed, despite the isomorphism of the two conditionals, the information processing in reasoning on them is different. We decided to study the reasoning under uncertainty, as it reflects reality more accurately. To do this, we analysed the coherence of participants using De Finetti’s theory for deduction under uncertainty. The results of our study show no significant difference in performance between Chinese and French participants, neither on the sufficient conditional nor on the necessary conditional. Thus, our hypothesis derived from the weak version of linguistic relativity is refuted. Our results confirm the second hypothesis in two out of three inference schemas.